2019
DOI: 10.1002/ejhf.1645
|View full text |Cite|
|
Sign up to set email alerts
|

Sex‐ and age‐related differences in the management and outcomes of chronic heart failure: an analysis of patients from the ESC HFA EORP Heart Failure Long‐Term Registry

Abstract: AimsThis study aimed to assess age-and sex-related differences in management and 1-year risk for all-cause mortality and hospitalization in chronic heart failure (HF) patients.Of 16 354 patients included in the European Society of Cardiology Heart Failure Long-Term Registry, 9428 chronic HF patients were analysed [median age: 66 years; 28.5% women; mean left ventricular ejection fraction (LVEF) 37%]. Rates of use of guideline-directed medical therapy (GDMT) were high (angiotensin-converting enzyme inhibitors/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
71
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 60 publications
15
71
0
6
Order By: Relevance
“…However, women have been historically included in a smaller proportion (around 30%) than men in clinical trials, and their therapeutic management and prognosis have been less studied. All this leads to a lower prescription in women of the treatments recommended by clinical practice guidelines [12,31,[40][41][42] and, for reasons not entirely clear, with lower average drug doses [9,[43][44][45]. Although information on drug doses used and on the LVEF of our patients were not available in our cohort, we confirmed, in general, the lower prescription of the specific treatments for HF in women.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…However, women have been historically included in a smaller proportion (around 30%) than men in clinical trials, and their therapeutic management and prognosis have been less studied. All this leads to a lower prescription in women of the treatments recommended by clinical practice guidelines [12,31,[40][41][42] and, for reasons not entirely clear, with lower average drug doses [9,[43][44][45]. Although information on drug doses used and on the LVEF of our patients were not available in our cohort, we confirmed, in general, the lower prescription of the specific treatments for HF in women.…”
Section: Discussionsupporting
confidence: 75%
“…Conde-Martel et al, among others, observed similar diuretics consumption in both sexes [23,26], whereas in other studies, greater use has been reported in men, despite women presenting with greater congestion [15,26,40]. The higher prevalence of ischemic heart disease and arrhythmias in men would justify the greater dispensation of anti-coagulation and anti-aggregation treatments, in line with the results of Dewan et al [26], who also found a greater use of statins [6,41]. In other studies, greater side-effects related to ACE inhibitors have been reported for women, such as cough or angioedema [5,43,46,47].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…19 Furthermore, dapagliflozin appears safe and effective in vulnerable elderly patients, as well as in those with impaired renal function (excluding patients with estimated glomerular filtration rate <30 mL/min/1.73 m 2 ), in whom up-titration of GDMT may be challenging. 68,69 A post-hoc analysis of the DAPA-HF trial demonstrated similar risk reductions in HF hospitalisation and mortality with dapagliflozin, irrespective of background HF therapy, including ACEi/ARB, beta-blockers, MRAs, ivabradine, sacubitril/valsartan, cardiac resynchronisation therapy and implantable cardioverter-defibrillators. 70 Furthermore, the results were consistent regardless of whether patients received ≥50% or <50% of guideline-directed target doses of ACEi/ARBs, beta-blockers, or MRAs.…”
Section: Empa-vision (Nct03332212)mentioning
confidence: 99%
“…Ageing is an established major determinant of adequacy and adherence to treatment and of survival in patients with HF. [8][9][10][11] Lainščak et al 12 evaluated age-and sex-related differences in HF management, mortality and hospitalization in the patients enrolled in the ESC HFA EORP HF Long-Term registry. Age >75 years was associated with underutilization of optimal medical therapy and with increased mortality.…”
Section: Demographic Variablesmentioning
confidence: 99%